Modeling-based determination of physiological parameters of systemic VOCs by breath gas analysis: a pilot study. (6th May 2015) - Unterkofler, Karl; King, Julian; Mochalski, Pawel; Jandacka, Martin; Koc, Helin; Teschl, Susanne; Amann, Anton; Teschl, Gerald
Abstract: In this paper we develop a simple two compartment model which extends the Farhi equation to the case when the inhaled concentration of a volatile organic compound (VOC) is not zero. The model connects the exhaled breath concentration of systemic VOCs with physiological parameters such as endogenous production rates and metabolic rates. Its validity is tested with data obtained for isoprene and inhaled deuterated isoprene-D5.